The rate of pointwise approximation of positive linear operators based on q-integer - Gupta, Vijay; Nowak, G. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
This paper is concerned with positive linear operators based on a q-integer. The rate of covergence of these operators are established. For these operators, we give Voronovskaya-type theorems and apply them to q Bernstein polynomials and q-Stancu operators.